Rasgo De Personalidad y Psicopatología En Mujeres Transgénero Consumidoras de Marihuana En la Ciudad de Ibagué - Estrada Aguirre, Laura Alejandra (Universidad Antonio Nariño, 2024)
The body becomes a tool of political control from birth, shaped by androcentric norms that mold and impact daily life through the adaptation to gender expectations. This impact is particularly noticeable in female bodies.